Arm's length provision of public services - Morten Bennedsen; Christian Schultz (Center for Economic Studies and ifo Institute (CESifo), 2007)
We analyze the economic consequences of strategic delegation of the right to decide between public or private provision of governmental service and/or the authority to negotiate and renegotiate with the chosen service provider. Our model encompass both bureaucratic delegation from a government to a privatization agency and electoral delegation from voters to a government. We identify two powerfull effects of delegation when contracts are incomplete: The incentive effect increases the incentive part of service providers' remuneration and we show that strategic delegation may substitute formal incentive contracts. The bargaining effect improves the bargaining position vis a vis a private firm with market power and leads to a lower price for the service.
Keywords: D72; L33; L97; 330; outsourcing; strategic delegation; incentives; incomplete contracting; market power; representative democracy; Öffentliche Dienstleistung; Privatwirtschaft; Öffentlicher Sektor; Marktmacht; Demokratie; Ökonomischer Anreiz; Theorie